The effect of nutritional status on host response to artificial coccidiosis challenge, health, productivity and caecal microbiome diversity in different types of poultry - Akinci, Ibrahim (2021)
The main objective of this thesis was to investigate the effect of Eimeria infection on host immune response, health, productivity and caecal microbiota at different nutritional levels in different types of poultry.